What causes the body roll in front-crawl swimming? - Yanai, T. (Journal of Applied Biomechanics, 2001)
This study was conducted to describe the kinematics of bodyroll and investigate whether bodyroll was propelled primarily by the turning effect of the fluid forces (external torque) or by the reaction effect due to the acceleration of the limbs. The performances of 11 competitive swimmers were recorded using two panning periscopes, and the three-dimensional movement of the subjects was reconstructed from digitized video recordings. The external torque acting on the whole body was determined as the first time-derivative of the angular momentum of the whole body. The reaction effect of limb acceleration was determined as the first time-derivative of the angular momenta of the limbs. Shoulder roll and hip roll angles changed synchronously with the stroke frequency but their amplitudes were substantially different, indicating that the bodyroll consisted of a roll of the entire torso and a twist of the torso. The overall contribution of the external torque was to propel bodyroll, while that of the reaction effects of limb accelerations was to resist bodyroll. These results clearly indicate that the primary source for propelling bodyroll was the external torque. Implications towards the mechanical interactions among bodyroll, stroke frequency, and forward propulsion in front crawl swimming were discussed.